The impact of online reviews on trust and hotel booking intentions among Chinese visitors in Thailand - Pattanapokinsakul, Kanyapat; Kattiyapornpong, Uraiporn; Angsumalee, Warakorn; Ditta-apichai, Morakot (Kasetsart Journal of Social Sciences, 2026)
The growth of social media platforms and Online Travel Agencies (OTAs) has made it easier for Chinese visitors to access and contribute to online reviews. Applying the Stimulus-Organism-Response (S-O-R) model, this study aims to understand how online reviews impact trust and hotel booking intentions among Chinese tourists in Phuket, Thailand. It investigates to what extent online reviews, including review quality and positive and negative reviews, impact the trust and hotel booking intentions of 400 Chinese tourists who booked hotels online. The Structure Equation Modeling (SEM) findings showed that positive and negative reviews strongly affect trust among Chinese tourists, while reviewing quality, negative reviews, and trust directly affect hotel booking intentions. This study provides valuable insights for hotels to understand Chinese tourists’ online booking behavior and intentions. It also highlights the influence of online reviews on Chinese tourists’ booking intentions, which aided in managing tourists’ overall services and experience in drawing Chinese tourists for hotel booking and tourism recovery.